Naptime with Theo & Beau - Shyba, Jessica (New York : Feiwel & Friends, 2015)
A collection of photographs taken by the author, of her son and puppy napping together.
Keywords: Children and animals -- Pictorial works -- Juvenile literature; Naps (Sleep) -- Pictorial works -- Juvenile literature; Photography of children -- Juvenile literature; Children and animals -- Pictorial works; Naps (Sleep) -- Pictorial works; Photography of children